Night club and social ills: the needs for preventive measures under syariah law in Selangor / Hazarul Iqram Rozahan, Mohd Falihin Kamil Mohd Sazali and Mohd Taufikrullah Rusli - Rozahan, Hazarul Iqram; Mohd Sazali, Mohd Falihin Kamil; Rusli, Mohd Taufikrullah (2011)
This research has been conducted in relation to the issue of the lacunae in Syariah Criminal Offences (State of Selangor) Enactment 1995 with regard to the offence on Muslims in Selangor who enters into night clubs. Under the enactment, offences stated consist of offences in relation to the 'aqidah, offences relating to the sanctity of the religion of Islam and its institution, offences relating to decency, miscellaneous offences, and offences relating to abatement and attempt. But it is nowhere stated in the enactment the offences in relation with the prohibition on Muslims in Selangor from entering into night clubs. This research will focus on the application of Syariah Law in Malaysia. The most crucial parts of the research are to determine the existence of the related provision and to seek for any preventive measures in relation to prohibition on Muslims in Selangor from entering into night club. The offences stated in the enactment will be reviewed in order to delve into the main focus of the research.